Konsep Tarbiyah Dalam Perspektif Pendidikan Islam Modern - Alfarisi, Salman Alfarisi (Edification Journal : Pendidikan Agama Islam, 2025)
The concept of tarbiyah in the perspective of modern Islamic education is an integration of Islamic values with contemporary or modern education. Tarbiyah is the core of education in Islam which emphasizes the development of human beings as a whole, both in terms of spiritual, intellectual, and moral. In the context of modern Islamic education, the concept of tarbiyah has been developed to remain relevant to the challenges of the times without abandoning its basic values. This article examines how tarbiyah is applied in today's approaches to Islamic education, by combining Islamic methods and modern approaches. The research was carried out using a library research methodology with a qualitative research type by collecting data from primary sources such as books or articles relevant to the discussion. The results of the study show that modern Islamic education through the concept of tarbiyah emphasizes the balance between knowledge, morals, and spirituality. In addition, the role of teachers as coaches (murabbi) remains the key in shaping the character of students. Tarbiyah is not just a process of transferring knowledge, but a process of forming a whole human being in accordance with Islamic values